2019
DOI: 10.1088/1748-9326/ab4d7f
|View full text |Cite
|
Sign up to set email alerts
|

Inverse estimation of NOx emissions over China and India 2005–2016: contrasting recent trends and future perspectives

Abstract: Bottom-up emission inventories can provide valuable information for understanding emission status and are needed as input datasets to drive chemical transport models. However, this type of inventory has the disadvantage of taking several years to be compiled because it relies on a statistical dataset. Top-down approaches use satellite data as a constraint and overcome this disadvantage. We have developed an immediate inversion system to estimate anthropogenic NO x emissions with NO 2 column density constrained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 50 publications
2
33
0
Order By: Relevance
“…watched in future, to assess its impact on BC transport to higher latitudes and/or snow albedo change. Itahashi et al (2019) recently found that NO x emission from NE China exhibited a later peak between 2013 and 2016, consistent to the tendency for BC. Region II (N-CEC) showed a CO decrease but only a very weak BC decrease, suggesting that the BC/CO emission ratio increased.…”
Section: Comparative Trends In Co Emissionssupporting
confidence: 61%
See 1 more Smart Citation
“…watched in future, to assess its impact on BC transport to higher latitudes and/or snow albedo change. Itahashi et al (2019) recently found that NO x emission from NE China exhibited a later peak between 2013 and 2016, consistent to the tendency for BC. Region II (N-CEC) showed a CO decrease but only a very weak BC decrease, suggesting that the BC/CO emission ratio increased.…”
Section: Comparative Trends In Co Emissionssupporting
confidence: 61%
“…Importantly, the balance or lag between SO 2 and BC reductions could have strong climate effects. Using satellite data inversion, emission reductions from China were estimated to be 24-33%, or (2.4-3.3)% y −1 for SO 2 during 2007-2016 (Qu et al, 2019) and (3.0-5.4)% y −1 for NO x during 2011-2016 (Itahashi et al, 2019). Our estimated BC emission reductions of 4.6% y −1 were nearly equal to or even faster than these rates.…”
Section: Tendency Of Atmospheric Black Carbon/pm25 Mass Concentratiomentioning
confidence: 65%
“…For the MAAP, measurements of reflectance at two angles, in addition to transmittance, were made with respect to the particleladen filter, and the built-in algorithm for radiative transfer enabled the separation of scattering from absorption (Petzold and Schönlinner, 2004). We demonstrated that the two instruments had a high level of agreement and compatibility at Fukue Island once the mass absorption cross section for the MAAP was modified from manufacturer's recommendation of (6.6) to 10.3 m 2 g −1 (Kanaya et al, 2013(Kanaya et al, , 2016. The filter-based observations were also successfully compared to an ECOC analyzer (Sunset Laboratory Inc., Tigard, Oregon, USA) in which BC was calibrated as CO 2 after combustion and to a Single Particle Soot Photometer (SP2; Droplet Measurement Technologies, Longmont, Colorado, USA) in which Alfa Aesar™ Fullerene soot (Fisher Scientific, part of Thermo Fisher Scientific, Leicestershire, England) particles with a known mass were used as a calibration standard (Miyakawa et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…In this context, long-term observations, which are based on reliable instruments with careful calibration, are desired to determine the BC emissions trends in China. We have been conducting such observations of BC and related species at Fukue Island since 2009 (Kanaya et al, 2013(Kanaya et al, , 2016Miyakawa et al, 2017). This site receives air masses from various latitudinal bands in China during the winter monsoon (effective from autumn to spring) with negligible effects from local sources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation